Cultural Aspects of Disposable Diaper Waste and Sanitary Napkins in Indonesia - Indah Yasminum Suhanti (Universitas Airlangga, 2021)
The cultural aspect of managing disposable diapers and sanitary napkins in Indonesia is very important. The purpose of this study was to obtain an overview of the cultural aspects of the waste management process. The method used literature review. The data analysis used thematic analysis. The articles obtained from the selection were 18 titles. The results of the review show that the culture that is most discussed in the issue of disposable diapers and sanitary napkin waste management is the culture of industrial society, then Javanese society, and the last one is colonial. Culture is discussed in the realm of practice and reasons for use as well as practices and reasons for waste management. Things that need to be deepened are culture in the form of (1) cultural engineering and cultural environment and (2) the realm of the impact of using and managing disposable diapers and sanitary napkins. Another suggestion is to expand database searches and perform SLRs for more detailed results.